Making Memories: The Development of Long-Term Visual Knowledge in Children with Visual Agnosia - Tiziana Metitieri; Carmen Barba; Simona Pellacani; Maria Pia Viggiano; Renzo Guerrini (Neural Plasticity)
There are few reports about the effects of perinatal acquired brain lesions on the development of visual perception. These studies demonstrate nonseverely impaired visual-spatial abilities and preserved visual memory. Longitudinal data analyzing the effects of compromised perceptions on long-term visual knowledge in agnosics are limited to lesions having occurred in adulthood. The study of children with focal lesions of the visual pathways provides a unique opportunity to assess the development of visual memory when perceptual input is degraded. We assessed visual recognition and visual memory in three children with lesions to the visual cortex having occurred in early infancy. We then explored the time course of visual memory impairment in two of them at 2 years and 3.7 years from the initial assessment. All children exhibited apperceptive visual agnosia and visual memory impairment. We observed a longitudinal improvement of visual memory modulated by the structural properties of objects. Our findings indicate that processing of degraded perceptions from birth results in impoverished memories. The dynamic interaction between perception and memory during development might modulate the long-term construction of visual representations, resulting in less severe impairment.